Cancer of the female lower genital tract - Eifel, Patricia J; Levenback, Charles (B.C. Decker, 2001)
Cancer of the Female Lower Genital Tract American Cancer Society Atlas of Clinical Oncology ACS This volume of the American Cancer Society Atlas of Clinical Oncology is intended to provide clinicians, students, and scientists with an integrated analysis and review of the biology, diagnostic evaluation, and treatment of cancers of the lower female genital tract. Recent changes in the accepted treatment for invasive cervical cancer, and in many aspects of the epidemiology, diagnosis, and evaluation of these cancers, make this discussion particularly timely.
Atlas of clinical oncology
Keywords: nádory vaginy; nádory ženských pohlavních orgánů; nádory vulvy; Vaginal Neoplasms; nádory děložního čípku; Genital Neoplasms, Female; gynekologie a porodnictví; Vulvar Neoplasms; onkologie; Uterine Cervical Neoplasms